Increased Circulating Levels of Ectodysplasin A in Newly Diagnosed Type 2 Diabetic Patients - Deng, Xia; Cai, Zhensheng; Li, Yanyan; Wu, Xunan; Zhao, Li; Li, Haoxiang; Chen, Ke; Zhang, Panpan; Wang, Chenxi; Zhao, Zhicong; Yang, Ling; Yuan, Guoyue (Frontiers in Endocrinology, 2021)
Objective: Etodysplasin A (EDA), a newly discovered hepatokine, has recently been considered to be closely related to glycolipid metabolism disorders, but the pathophysiological effects of EDA are still poorly understood. This study was the first time to determine the level of serum EDA in newly diagnosed type 2 diabetes mellitus (T2DM) patients, and to explore the relationships between serum EDA levels and various metabolic indexes. Methods: A total of 184 subjects were enrolled in the study, including 92 subjects with newly diagnosed T2DM and 92 subjects with age- and sex- matched normal glucose tolerance (NGT). Serum EDA levels were determined using enzyme-linked immunosorbent assay (ELISA). And oral glucose tolerance test, glycosylated hemoglobin c(HbA1c), and insulin were also measured. Results: Serum EDA levels were significantly increased in the T2DM group than in the NGT group (359.91 ± 117.99 vs. 265.82 ± 86.51pg/mL, P<0.001). Serum EDA levels were positively correlated with body mass index (BMI), waist-to-hip ratio (WHR), fasting plasma glucose (FPG), HbA1c, 2-hour postprandial plasma glucose(2hPG), fasting plasma insulin (FIns), fasting C peptide (FCP), triglyceride (TG), HOMA-IR, and negatively correlated with high-density lipoprotein cholesterol (HDL-c) and HOMA-β (P<0.05). Multiple stepwise regression analysis demonstrated that 2hPG and FIns were independent influencing factors of serum EDA level (P<0.05). Logistic regression analysis showed that serum EDA level was significantly independent correlated with T2DM (P<0.05). Conclusions: Serum EDA level are significantly higher in T2DM patients, indicating that circulating EDA may be involved in the pathogenesis of T2DM.